«Verità ed errore senza fine». Alcune riflessioni sull’opinione pubblica e la stampa in Hegel e Gramsci - Destasio, Alberto (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
This paper explores the concept and role of public opinion in the modern political world. First of all, we analyse the concepts of öffentliche Meinung and Presse in Hegel’s Philosophy of right (§§ 316-319). This hegelian reflexion will have a decisive impact on the further philosophical debate on the same matter. In the second part of this paper, we address the theoretical and political Wirkungsgeschichte of hegelian theory of öffentliche Meinung in in some philosophers of 21st century (Lukács, Adorno Gramsci, Spengler). Hegel; Gramsci; Public Opinion; Ideology; Press.